Evaluación del progreso en la selección de líneas resistentes al añublo del arroz (Pyricularia oryzae Cav.) en viveros internacionales - Guimarães, Elcio Perpétuo; Ospina Rey, Yolima (1992)
The CIAT rice breeding program has been developing germplasm resistant to P. oryzae since 1967. The distribution of these lines throughout Latin America is done using the observational nursery (VIOAL) organized by the International Network for Genetic Evaluation of Rice-INGER. Augmented design with 11 blocks and 5 checks was used to evaluate 638 lines coming from five nurseries distributed during the period 1985-1989. The objective is to analyze the reaction of these lines to rice blast under the same disease pressure and to determine the progress of selection for resistance in rice lines included in nurseries during this five year period. The result show that progress was made, there was a significant decrease in susceptibility, both at leaf and panicle level, in the nurseries distributed after 1985, emphasizing the importance of the evaluation and selection site.